Abses Hepar: Analisis Kasus dan Tinjauan Penanganannya - Matatula, Christian Nugraha; Nikijuluw, Helfi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Hepatic abscess is the most common type of visceral abscess. The annual incidence of hepatic abscess is reported to be 2.3 cases per 100,000 population, with a higher incidence in men compared to women. In this case, a 22-year-old male patient presented to the emergency department of Haulussy Regional General Hospital with complaints of generalized abdominal pain. Laboratory results showed a decrease in hemoglobin and lymphocytes, while leukocyte levels were elevated. Urea and SGPT levels were also increased, whereas albumin levels were decreased. The medical management provided to the patient in this case included surgical intervention in the form of exploratory laparotomy. Exploratory laparotomy is a surgical procedure performed by making an incision in the peritoneal cavity to allow the surgeon to directly visualize or inspect the internal organs of the abdomen. The procedure aims to obtain a clear view of the patient's abdominal condition, which cannot be definitively assessed through non-invasive examinations such as imaging studies.